Environmental impact of aquaculture in Greece. Practical experiences - Klaoudatos S.D. (Environmental impact assessment of Mediterranean aquaculture farms, 2001)
The general background of the aquaculture activities in Greece with reference to the cultivated species, systems, production areas, and prospects are presented. Also, the legal-planning-management frame in which the aquaculture industry is being installed and operated is here presented. A view about the conflicts between aquaculture and other activities in the same coastal area, with the influence of this particular situation on the development of the aquaculture industry is mentioned. The agencies (Governmental services) which are involved for the collection, analysis and estimation of the future results from the installation and operation of a fish farm in a given area, are also mentioned. Moreover, there is a presentation of the methods and the research for the estimation of the interaction of the aquaculture activities and the sea environment. Finally, the estimation of the present situation and the future trends of the aquaculture industry in Greece are presented.
TECAM Seminar on Environmental Impact Assessment of Mediterranean Aquaculture Farms, 2000/01/17-21, Zaragoza (Spain)